1991
DOI: 10.1007/bf02781685
|View full text |Cite
|
Sign up to set email alerts
|

A case of HBs antigen negative fulminant hepatitis with IgM antibody to hepatitis B core antigen persisting more than seven years

Abstract: A 33-year old dentist developed fulminant hepatitis. At admission, a test for IgM antibody to hepatitis B core antigen (IgM anti-HBc) was positive, while tests for HBsAg and HBeAg were negative. He was cured of the disease, but in follow-up examinations from 1983 to 1990 IgM anti-HBc was continuously detected with radioimmunoassay while HBsAg and HBV-DNA were absent in the serum. However, HBcAg was found in a biopsied liver specimen and a small quantity of HBV-DNA was detectable by polymerase chain reaction as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…It has been suggested that HBeAg can be more easily transmitted via placenta than HBsAg in that it is smaller than the latter and is free from agglutination [14] . HBeAg or the compound of HBeAg and α-HBeIgG can pass the barrier of placenta by means of active-transfer in human body [15] . One study also showed that some babies of HBV infected mothers were HBeAg positive and HBsAg negative in femoral blood at birth, and HBsAg titres of the mothers were significantly higher than HBeAg titres (200 times or more).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that HBeAg can be more easily transmitted via placenta than HBsAg in that it is smaller than the latter and is free from agglutination [14] . HBeAg or the compound of HBeAg and α-HBeIgG can pass the barrier of placenta by means of active-transfer in human body [15] . One study also showed that some babies of HBV infected mothers were HBeAg positive and HBsAg negative in femoral blood at birth, and HBsAg titres of the mothers were significantly higher than HBeAg titres (200 times or more).…”
Section: Discussionmentioning
confidence: 99%